IDENTIFIKASI KEMAMPUAN KERJASAMA ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL - Dewi Trismahwati; Nur Indah Sari (LPPM STAI DARUSSALAM LAMPUNG, 2020)
Current of globalization can affect the nation's cultural identity. One of the national cultures affected by the current of globalization is a traditional game. Traditional games besides being played safely from various ages are a characteristic of national culture that has various benefits and has character values that can be developed, one of the behaviors that exist in traditional games is cooperative behavior. Since early childhood cooperation behavior needs to be instilled in order to prepare active children for their future in the community. The purpose of this study was to analyze children's cooperative behavior through traditional games. The research method in writing is qualitative research. The results showed that children's cooperative behavior could be seen from traditional games. children become interactive, communicative and foster a sense of togetherness and mutual help.